Hubungan antara Polifarmasi dan Kepatuhan Pasien dengan Multimorbiditas di RSUD dr R Goeteng Taroenadibrata Purbalingga - Arum Nur Hidayatun; Sunarti Sunarti; Rani Prabandari (Jurnal Sehat Mandiri, 2024)
has a major impact on a person's quality of life. Patients with multimorbidity have the potential to prescribe polypharmacy. This study aims to determine the level of patient adherence and the relationship between polypharmacy and adherence of multimorbid patients at the Internal Medicine Clinic RSUD dr R Goeteng Taroenadibrata Purbalingga. A cross-sectional study using the convenience sampling method was conducted on 342 multimorbid patients receiving polypharmacy prescriptions. Data were collected using demographic questionnaires and the Morisky Medication Adherence Scale (MMAS-8) questionnaire. The average age of the respondents in this study was 57.81 ± 10.596, with an average patient taking 9.8 ± 3.2 drugs per day and having an average diagnosis / number of diseases suffered 3.56 ± 1.06 diagnoses. Patients with low adherence category were 106 people (31%), medium were 125 people (36.5%) and high were 111 people (32.5). Conclusion: There is a significant relationship between polypharmacy (p<0.05) and adherence to taking medication in multimorbid patients (p=0.000), where the more medication the patient gets (polypharmacy), the lower the patient's compliance in taking medication. It is recommended that the hospital carry out evaluations and interventions to improve treatment compliance.